Enhancing thermal properties of asphalt materials for heat storage and transfer applications - Dawson, Andrew R.; Dehdezi, Pejman Keikhaei; Hall, Matthew R.; Wang, Junzhe; Isola, Riccardo (Taylor & Francis, 2012)
The paper considers extending the role of asphalt concrete pavements to become solar heat collectors and storage systems. The majority of the construction cost is already procured for such pavements and only marginal additional costs are likely to be incurred to add the necessary thermal features. Asphalt concrete pavements are, therefore, designed that incorporate aggregates and additives such as limestone, quartzite, lightweight aggregate, copper slag and copper fibre to make them more conductive, or more insulative, or to enable them to store more heat energy. The resulting materials are assessed for both mechanical and thermal properties by laboratory tests and numerical simulations and recommendations are made in regard to the optimum formulations for the purposes considered.